Growth Performance Cachama (Colossoma macropomum) Fished by Polyculture with Taiwan Kijing (Anodonta woodiana) - Zaky, Praduta; Putra, Iskandar; Masjudi, Heri (Jurnal Perikanan dan Kelautan, 2025)
Cachama (Colossoma macropomum) is a freshwater fishery commodity with high economic value, but water quality in cultivation is often an obstacle. The utilisation of natural biofilters, such as Taiwanese mussels (Anodonta woodiana), in a polyculture system is expected to improve water quality and increase fish growth performance. This study aims to evaluate the effect of different numbers of Taiwanese mussels in a polyculture system on the growth of Cachama. The study was conducted for 56 days using a completely randomised design (CRD) with four treatments: P0 (without biofilter), P1 (14 mussels), P2 (19 mussels), and P3 (24 mussels), with three replications for each treatment. The parameters observed include absolute weight growth, absolute length, specific growth rate, survival, and water quality. The results showed that the P3 treatment gave the best results with an absolute weight of 8.25 g, an absolute length of 4.78 cm, and a specific growth rate of 2.02% per day. The use of Taiwanese mussel biofilters significantly improved water quality and growth of cachama.